EFEKTIVITAS Trichoderma sp. DAN Gliocladium sp. DALAM PENGENDALIAN LAYU FUSARIUM PADA TANAMAN KRISAN - Hartal Hartal; Misnawaty Misnawaty; Indah Budi (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2010)
[THE EFFECTIVENESS OF Trichoderma sp. AND Gliocladium sp IN CONTROLLING FUSARIUM WILT ON CHRYSANTHEMUM]. Fusarium wilt is a major soil borne disease in chrysanthemum, which results in yellowing and permanent wilt on the plant. The disease has capability to remains intact in the soil for years so that preventive operation prior planting often fail to provide fusarium-free environment for the plant. The elaboration of use of antagonistic organisms as the biological agents may provide an effective solution for controlling the disease. Objective of this study was to evaluate the effectiveness of two species of fungi, Trichoderma sp. and Gliocladium sp.,  as the antagonistic agents for controlling the development of fusarium wilt on chrysanthemum. Both fungi were applied singly or in combination onto the fusarium inoculated soil which were prepared as growing media for chrysanthemum plants. Results indicated that Trichoderma sp. and Gliocladium sp. were effective in controlling the development of fusarium wilt in krisan, where application of  combined antagonistic agents had produced the highest suppression to the fusarium development (70.1 %), followed by single application of Trichoderma sp. (56.4 %) and Gliocladium sp. (55.9 %).